Automated immature granulocyte count in patients of the intensive care unit with suspected infection - Letícia R. Lima; Gustavo S. P. Cunha; Keite S. Nogueira; Samuel Ricardo Comar
ABSTRACT Introduction: Diagnosing infections in intensive care unit (ICU) patients is vital to provide appropriate therapies. Hematological analyzers perform automated immature granulocyte counts (IG) quickly and with no additional cost when compared to traditional microbiological cultures. Elevated IG is directly associated with infections and inflammation. Objectives: Evaluate IG as infection marker in adult inpatients at the ICU-Complexo Hospital de Clínicas da Universidade Federal do Paraná (CHC-UFPR), compared to cultures of biological materials (gold standard). Material And Methods: Samples of 200 adult inpatients at CHC-UFPR ICU with suspected infection were used. Absolute (IG#) and relative (IG%) counts were performed on the Sysmex XN-3000. Cultures and blood cultures were performed either manually or on Bactec FX. Diagnostic accuracy and agreement for IG# and IG% were evaluated. Results: The reference intervals (RI) obtained for IG# and IG% were 0.06 × 103/µl and 0.6%, respectively, with sensitivity for both of 74.4% and specificity of 25.3% for IG#, and 26.6% for IG%. The receiver operating characteristic (ROC) curve showed cut-off value of 0.33 × 103/µl for IG#, sensitivity of 28%, specificity of 82.3%, and area under the curve (AUC) of 0.521. For IG%, cut-off value was 1.35%, sensitivity 44.6%, specificity 64.6%, and AUC 0.532. CV < 3% increased specificity to 88%. Conclusion: RI of IG% and IG# showed high sensitivity and are useful in screening for infection in ICU patients. The CVs demonstrated by the ROC curves showed high specificity and are helpful on the exclusion of sepsis diagnosis in ICU patients. IG was shown to be useful for screening and confirmation of infection in ICU patients.